Idiopathic Vanishing Bile Duct Syndrome in a Young Female: A Case Report - Min Ji Kim; Hyun Myung Cho; Young Mi Hong; Ki Tae Yoon (The Korean Journal of Gastroenterology)
Vanishing bile duct syndrome (VBDS) is characterized by the progressive loss and destruction of the intrahepatic bile ducts, leading to bile stasis and associated symptoms such as jaundice. This condition is commonly associated with drug side effects, infections, neoplasms, and autoimmune diseases, but the precise mechanism of its development is unclear. Although VBDS can be diagnosed based on the patient's symptoms and disease progression, a liver biopsy is essential for confirmation, and the prognosis can vary significantly. This paper presents a rare case of a young female patient diagnosed with idiopathic VBDS after undergoing a liver biopsy to investigate unexplained jaundice. The patient's liver function improved partially after an ursodeoxycholic acid and prednisolone treatment.